2013
DOI: 10.1063/1.4774024
|View full text |Cite
|
Sign up to set email alerts
|

Surface temperature effects on the dynamics of N2 Eley-Rideal recombination on W(100)

Abstract: Quasiclassical trajectories simulations are performed to study the influence of surface temperature on the dynamics of a N atom colliding a N-preadsorbed W(100) surface under normal incidence. A generalized Langevin surface oscillator scheme is used to allow energy transfer between the nitrogen atoms and the surface. The influence of the surface temperature on the N(2) formed molecules via Eley-Rideal recombination is analyzed at T = 300, 800, and 1500 K. Ro-vibrational distributions of the N(2) molecules are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 85 publications
2
51
0
Order By: Relevance
“…ER recombination is considered to take place whenever both hydrogen atoms reach the initial altitude of the projectile with a positive H 2 center-of-mass momentum along Z, an inter-atomic distance r ≤ 2.2 Å after only one rebound of the diatom center-of-mass along the trajectory. 83,84 In order to compare our results with experimental data, 10 we have also performed QCT calculations using a generalized Langevin oscillator (GLO) model [85][86][87][88][89] to account for surface temperature effects and energy exchange with phonons. 83,84 However, we have found that adding such ingredients in the dynamics simulations barely alter the results obtained within the rigid surface approximation (at least, as far as the total ER reaction cross sections and products energy distributions are concerned).…”
Section: A Methodology and Computational Detailsmentioning
confidence: 99%
“…ER recombination is considered to take place whenever both hydrogen atoms reach the initial altitude of the projectile with a positive H 2 center-of-mass momentum along Z, an inter-atomic distance r ≤ 2.2 Å after only one rebound of the diatom center-of-mass along the trajectory. 83,84 In order to compare our results with experimental data, 10 we have also performed QCT calculations using a generalized Langevin oscillator (GLO) model [85][86][87][88][89] to account for surface temperature effects and energy exchange with phonons. 83,84 However, we have found that adding such ingredients in the dynamics simulations barely alter the results obtained within the rigid surface approximation (at least, as far as the total ER reaction cross sections and products energy distributions are concerned).…”
Section: A Methodology and Computational Detailsmentioning
confidence: 99%
“…The competition between the e-h pairs and phonon channels governs the relaxation dynamics of the transient hot species, and thus it plays a decisive role in the system reactivity properties. The reason is that it rules the traveled length and relaxation time of a hot atom or molecule on the surface and, consequently, the probability to undergo a recombination reaction with another adsorbate [18][19][20][21][22][23].Recent ab initio molecular dynamics (AIMD) simulations with electronic friction (AIMDEF) have shown that e-h pair excitations are the dominant relaxation mechanism for hot H atoms on Pd(100) that originate from the dissociative adsorption of H 2 [16]. More particularly, this channel dissipates energy at a five times faster rate than the phonon channel [10].…”
mentioning
confidence: 99%
“…The competition between the e-h pairs and phonon channels governs the relaxation dynamics of the transient hot species, and thus it plays a decisive role in the system reactivity properties. The reason is that it rules the traveled length and relaxation time of a hot atom or molecule on the surface and, consequently, the probability to undergo a recombination reaction with another adsorbate [18][19][20][21][22][23].…”
mentioning
confidence: 99%
“…The former mechanism involves direct collision between a scattering atom (projectile) and an adsorbed species (target), 30 while the latter is governed by hyperthermal diffusion of the projectile onto the surface prior to abstraction. 31 The influence of the crystal face has been recently scrutinized theoretically for the Eley-Rideal (ER) recombination a) pascal.larregaray@u-bordeaux.fr of hydrogen and nitrogen on the W(100) and W(110) surfaces, [32][33][34][35][36] accounting for dissipation to surface phonons and electrons. 37 In these direct ultrafast processes, the surface is thought to mostly behave as a spectator.…”
mentioning
confidence: 99%
“…Such a structure is much smaller and less extended on W(110) and consequently affects much less ER reactivity as a function of the incidence energy. [32][33][34] H 2 ER abstraction on tungsten also reveals distinct recombination mechanisms depending on the surface structure. On W(110), recombination occurs after rebound of the projectile on the W surface atoms in the close vicinity of the target.…”
mentioning
confidence: 99%